Understanding the fouling/scaling resistance of superhydrophobic/omniphobic membranes in membrane distillation - Liu, Li; Xiao, Zechun; Liu, Yongjie; Li, Xuemei; Yin, Huabing; Volkov, Alexey; He, Tao (Desalination, 2021)
Membrane distillation has shown great promises in desalinating various water streams. Significant progresses have been made in the past decades owing to the development of advanced membrane materials, such as superhydrophobic and omniphobic membranes. However, fouling and scaling remains a critical issue for stable operation. This account summarizes contemporary theories in fouling and scaling formation and their limitations in explaining the fouling resistance of superhydrophobic and omniphobic membranes. A new understanding is proposed based on hydrodynamics where non-slip boundary conditions play a critical role. By distinguishing a pinned and suspended wetting state, it is suggested that a superhydrophobic or omniphobic membrane correlates to a suspended wetting state, consequently a slip surface leading to scaling/fouling resistance. A new framework for analyzing the fouling/scaling behavior of MD membrane is provided to identify the wetting and hydrodynamic character of the membrane. A novel concept of treating the highly saline waste streams is suggested to cover membrane synthesis, module design and process optimization. The present work will be of interest to scientists and engineers searching for solutions to the MD fouling issues. •New understanding of fouling/scaling resistance of superhydrophobic membranes was proposed.•Water-air-solid interface with suspended wetting incurs potential slippage.•Sustaining suspended wetting and slippage is critical for antifouling and antiscaling.•Conventional thermodynamic theories for fouling/scaling are special case of non-slip.